Factors influencing consumer perceived risks towards online purchase intention of electronic products in Malaysia - Muhammad Shahrir bin Mohamed Shafieek (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Online purchase is the method of consumers' obtaining products and services that will satisfy their needs. It is essential to understand the ultimate motive behind the transaction made by consumers and it is also important for suppliers and retailers to target the right channel to reach out to their customers. Therefore, in order to survive in this modern and competitive marketplace, it is crucial to understand the factors influencing consumers' perceived risks towards online purchase intention especially during the purchase decision process. Taking this into consideration, the research at hand has been crafted with the ultimate objective of unveiling the risks that are affecting consumers when purchasing through online, giving special attention to the Malaysian consumers particularly in purchasing electronic products. In order to do so, this study has greatly relied on the framework that has been derived from previous literatures. In addition to this empirical study, all the data had been collected through a self-administered questionnaire via e-survey from 225 consumers residing in Malaysia. Data collected from the respective respondents have been analyzed through the means of Statistical Package for Social Sciences (SPSS) software. As for the data analysis, particularly descriptive analysis, reliability test, exploratory factor analysis (EFA), and regression analysis will be conducted through SPSS. Results of this study indicates that among all the five factors, three factors have influential effect towards online purchase intention, which are privacy risk, psychological risk, and financial risk. The other two, performance risk and social risk, do not strongly influence online purchase intention of electronic products in Malaysia. Therefore, online vendors and suppliers should be focusing more on reducing customers' perceived risk towards privacy, psychological, and financial to increase their customers' purchase intention towards online offerings. Additionally, online marketers should be more concerned about these attributes to increase customers' intention to purchase through online which will increase customer loyalty in the long run. The findings derived from this study are to facilitate marketers in the creation of effective marketing strategies in engaging consumers to purchase through online rather than offline. This can be achieved by reducing the factors that are influencing consumers' perceived risks. At the same time, the findings have potential values to academicians as well as consumers at large.